Downlink Performance of Optical Power Domain NOMA for Beyond 5G Enabled V2X Networks - Singh, Gurinder; Srivastava, Anand; Bohara, Vivek Ashok; Liu, Zilong (IEEE open journal of vehicular technology, 2021)
In this work, we explore the potential benefits and practical challenges associated with implementation of optical power domain non-orthogonal multiple access (OPD-NOMA) scheme for visible light communications (VLC) based vehicle-to-everything (V2X) networks with a major aim of providing vehicles with reliable, ubiquitous, and massive connectivity. In the proposed framework, an installed light source (e.g., traffic lamp post or street light lamp post) broadcasts a safety related message to desired nodes through visible light. However, such VLC transmission is subject to interference originating from the vehicles in the adjacent lane. Using the stochastic geometry approach, we model the locations of vehicles on the road via Poisson point process. We investigate the applicability of downlink OPD NOMA enabled V2X network for typical infrastructure-to-vehicle (I2V) communication in presence of interference caused from concurrent vehicle-to-vehicle (V2V) transmissions with an aid of stochastic geometry. Through the obtained results, it has been shown that the downlink OPD NOMA based V2X network offers improved performance in terms of outage performance and average achievable rate as compared to the conventional RF based V2X communication.